The role of extended synaptotagmin at membrane contact sites in cancer research - Pan, Yuetian; Strohmer, Dorothee; Feng, Shikai; Zhang, Guibin; Cui, Hongshang; Song, Yongbin (Frontiers in Cell and Developmental Biology, 2023)
Membrane contact sites (MCSs) are adjacent locations between the membranes of two different organelles and play important roles in various physiological processes, including cellular calcium and lipid signaling. In cancer research, MCSs have been proposed to regulate tumor metabolism and fate, contributing to tumor progression, and this function could be exploited for tumor therapy. However, there is little evidence on how MCSs are involved in cancer progression. In this review, we use extended synaptotagmins (E-Syts) as an entry point to describe how MCSs affect cancer progression and may be used as new diagnostic biomarkers. We then introduced the role of E-Syt and its related pathways in calcium and lipid signaling, aiming to explain how MCSs affect tumor proliferation, progression, metastasis, apoptosis, drug resistance, and treatment through calcium and lipid signaling.Generally, this review will facilitate the understanding of the complex contact biology of cancer cells.Cancer is the second most important cause of death worldwide and is likely to overtake ischemic heart disease as the leading cause by 2060.(1) For many tumors, effective therapy is lacking, and novel treatment approaches are urgently needed. MCSs are an underinvestigated research topic with the potential to identify new targets for anticancer therapy. Therefore, this review seeks to compile the current knowledge and explain potential future applications of MCSs.The endoplasmic reticulum (ER) is a complex cellular network. The ER is involved in endocytosis, exocytosis and, indeed, all membrane functions via vesicle transport. However, these sites of vesicle transport exhibit only membrane contact without membrane fusion.(2) These contact sites are called MCSs, and they allow the direct exchange of macromolecules. They also maintain stability between organelles and even intracellular homeostasis, making them possibly exploitable for cancer treatment.(3) However, the mechanism of MCSs in tumor metabolism is still unclear. This paper